Official Japan Pavilion Post Card
Japan Pavilion, symbolized in this replica of a feudal castle, depicts its rich culture in a harmonious blend with its modern industrial arts and exhibits. Amid a garden of serenic beauty visitors enjoy a bit of Japan transplanted in America.